Electrocardiographic parameters of the American Miniature Horse: Influence of age and sex - Santarosa, Bianca P. [UNESP]; Lourenço, Maria L.G. [UNESP]; Dantas, Gabriela N. [UNESP]; Ulian, Carla M.V. [UNESP]; Heckler, Marta C.T. [UNESP]; Sudano, Mateus J.; Gonçalves, Roberto C. [UNESP]; Chiacchio, Simone B. [UNESP] (FapUNIFESP (SciELO), 2016)
The veterinary cardiology has growing importance in equine medicine. There are studies of standardization of electrocardiographic parameters of many races, according to their stature and ability. However, no studies are in the literature with the American Miniature Horse. To evaluate the electrocardiogram (ECG) tracing configuration of this breed at rest and to verify the influence of age and sex on ECG parameters, 203 horses including 143 females and 60 males were divided into four age groups (foals, yearlings, adults and elderly). Electrocardiographic parameters were performed by computerized electrocardiogram (TEB), and the parameters were evaluated in six leads of frontal plane (Lead I, II, III, aVR, aVL and aVF) and base-apex (BA). Heart rates (HR) decreased with increasing age were higher in males than in females. Sinus tachycardia followed by sinus arrhythmia was dominant in both sexes. The cardiac axis was higher in males and ranged between 120° and 150° for foals, 30° and 60° for yearlings and adults, and 60° and 90° for the elderly. The P wave was bifid in several animals. The P-wave amplitude and T-wave duration from lead II and BA were larger in males than in females. The majority of the animals exhibited ST segment depression and a negative T-wave. The most common QRS complex morphology was Qr. Differences were observed between the electrocardiographic tracings of males and females, and age influenced the ECG parameters. Therefore, this study established the ECG patterns for the American Miniature Horse breed and could be used to determine the influence of age and sex on several of the studied variables.
Keywords: Age; Electrocardiogram; Equine; Ponies; Sex